Telemedicine in COVID-19 era (BIRDEM Medical Journal, 2020)
Background: COVID-19 pandemic has set many things to new normal. Telemedicine, in its modern form, started in the 1960s. In this COVID era of isolation, lockdown and quarantine, telemedicine has emerged as an essential way to seek medical consultation. This study was designed to explore the practical utility of telemedicine.Methods: This was an observational study of real-life scenario. The data were collected from prescriptions of single, home-based, specialist clinical practice set-up. It was over a period of 26 days in the month of August 2020. The liking or disliking or preference of telemedicine was asked by the physician and was recorded. Emergency cases were not entertained. Repeat visit cases were not included in statistical analysis. The data were analyzed by SPSS 23.Results: A total of 453 cases were analysed. There were 40 COVID-19 cases and 413 non-COVID cases. COVID and non-COVID cases were analysed in different account. Thirty (75%) COVID-19 cases were RTPCR positive; asymptomatic (2, 5%), influenza-like illness (ILI) (16, 40%) and pneumonia (22, 55%). Thirty one (77.5%) were diabetic, 19 (47.%) had hypertension, 4 (10%) had bronchial asthma. Twenty four (60%) cases were treated with regimen following national guideline (dexa+antibiotic+enoxaparine). Non-COVID cases were with chronic diseases; diabetes mellitus (81.6%), hypertension (67.1%), bronchial asthma (9.2%), hypothyroidism (12.6%). Nearly half (45.8%) were insulin user. Among the respondants, 8.4% disliked service of telemedicine, 91.6% supported it but 41.9% expressed the wisdom of face to face consulation. Over half (51.8%) urged not to abandone it.Conclusion: Telemecinie may be a useful way of medical consultation where needed and indicated.Birdem Med J 2020; 10, COVID Supplement: 74-80